New data evaluation procedure including advanced background subtraction for radiography using the example of insect mandibles. (May 2016) - Mangold, Stefan; van de Kamp, Thomas; Steininger, Ralph
Abstract: The usefulness of full field transmission spectroscopy is shown using the example of mandible of the stick insect Peruphasma schultei. An advanced data evaluation tool chain with an energy drift correction and highly reproducible automatic background correction is presented. The results show significant difference between the top and the bottom of the mandible of an adult stick insect.